An Analysis of the Evolving Asean-China Trade Linkages - Mendoza, Ronald U (Archīum Ateneo, 2015)
Whether China is a strategic trade partner or competitor to the ASEAN economies has remained unclear five years since the implementation of the ASEAN-China Free Trade Area in January 2010. The ASEAN economies and China are in an interesting position as both are experiencing growing bilateral trade while simultaneously competing in the production and export of major goods to similar trade destinations. This paper reviews Chinese-ASEAN trade statistics in order to provide an assessment of the economic importance of China to ASEAN and vice versa. It seeks to understand whether the trade relations between the two regions are evolving to be competitive or complementary. It discusses the restructuring regional production chain, citing anecdotal evidences, to illustrate opportunities for ASEAN economies to promote reciprocity and mutual growth with China. This paper argues that managing the competition and enhancing the complementarities could be an effective response in dealing with the realities of an advancing ASEAN-China economic integration and promoting mutual and broadbased gains.